Zur indianischen Landwirtschaft im Siedlungsgebiet der Kallawayas (Bolivien) - Mahnke, Lothar (ERDKUNDE, 1982)
Thanks to their particular location within the Cordilleras, the altitudinal stages in the Kallawaya valley follow one another at close intervals. The agrarian structure is well adapted to the natural conditions, especially in its surviving pre-Spanish elements; the most important aspects of adaptation being cultivation on terraces, the use of the taclla (and of the hoeing plough), intensification with the aid of irrigation, conservation of tuber crops, the crop rotation system and the aid of fallow periods, and distribution of cultivation areas over different altitudinal levels. Outside influences are liable to led to rapid disturbance of the ecological equilibrium.